Household pesticide exposure: an online survey and shelf research in the Metropolitan Region of Rio de Janeiro, Brazil - Leandro Lopes da Silva Galdiano; Valéria Troncoso Baltar; Silvia Polidoro; Valentina Gallo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: This study aimed to estimate household pesticide exposure in adult individuals in the Metropolitan Region of Rio de Janeiro, Brazil, and to verify the accessibility of these products in local and online businesses. The data were collected by an online questionnaire (1,015 responses) and a shelf survey in physical and online stores. Among the responses analyzed, 87.5% used pesticides in the previous year, most of which against mosquitoes (64.7%). The most common application method was aerosol spray (38.1%), and the most frequent places of use were bedrooms (29.7%) and living rooms (22.1%). About 30% of respondents reported invasion of pests, and the most common pests were ants (79.1%) and cockroaches (40.4%). Service area (71.6%) and kitchen (17.5%) were the most common storage locations. Approximately 91% of those who lived with children aged under 18 used pesticides. The use of chemical group of pyrethroids prevailed (81.6%), and 90.8% of the reportedly used products are class II [55.7% (highly toxic)] or class III [35.1% (medium toxic)]. The most significant amount of purchased products was in the pest category, followed by mosquitoes. More variety of products were available in online stores than in physical stores. The high exposure of the population to pesticides at household is a public health issue and confirms the need for studies that better assess the risks and consequences of chronic and low-dose exposure to these substances. It is essential to inform the population about the uncertainties and potential risks of indiscriminate use so that they can choose whether to use pesticides in their households.